Conventional deep pressure algometry is not suitable for clinical assessment of nociception in painless diabetic neuropathy. Issue 1 (1st January 2016) - Chantelau, Ernst A.
Abstract : Background: In diabetic persons with painless neuropathic foot ulceration, foot skin was found to be insensate to noxious pinprick stimulation (stimulation area less than 0.05 mm 2 ), while compression of deep subcutaneous foot tissues by Algometer II ® (stimulation area 1 cm 2 ) could evoke a deep dull aching. To elucidate this discrepancy, the Algometer II stimulation technique was critically reviewed by varying probe sizes and anatomical sites in the same study population 3 years later. Methods: Ten control subjects without neuropathy and 11 persons with painless diabetic neuropathy (PLDN, seven of whom with diabetic foot syndrome, i.e., past painless foot ulcer, or inactive Charcot arthropathy) were re-examined using Algometer II. Deep pressure pain perception threshold (DPPPT) was measured in random sequence with stimulation areas of 0.5 cm 2, 1 cm 2, and 2 cm 2 (separated by 5 min intervals), at the plantar forefoot, the instep, and the hindfoot of both legs. Results: In the control and PLDN groups, median DPPPTs differed significantly between stimulation areas (highest with 0.5 cm 2, intermediate with 1 cm 2, lowest with 2 cm 2 ; p< 0.001), and varied moderately by anatomical site. Between-group differences were relatively small. Results of the 1 cm 2 assessments repeated 3 years apart were similar. Conclusions: Algometer II readings represent spatial summation of low-threshold pressure-receptor rather than of high-threshold nociceptor stimulation and are, thus, unhelpful for assessing PLDN. Reproducibility of the measurements is good.